2010
DOI: 10.1038/mt.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Oncolytic Viral Replication Prevents Antiviral Immune Response and Toxicity, but Does Not Improve Antitumoral Immunity

Abstract: Oncolytic infection elicits antitumoral immunity, but the impact of tumor-selective replication on the balance between antiviral and antitumoral immune responses has not yet been investigated. To address this question, we constructed the highly tumor-selective adenovirus Ad-p53T whose replication in target tumor cells is governed by aberrant telomerase activity and transcriptional p53 dysfunction. Telomerase-dependent or nonselective adenoviruses were constructed as isogenic controls. Following infection of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…In contrast to rdAd, the unselective Ad5-WT and the tumor-selective hTert-Ad induced similar lysis in all investigated tumor cells in vitro and in vivo (data not shown). Interestingly, we observed no significant difference between hTert-Ad and Ad5-WT in ODC (Figure 6), in agreement with our previously described findings that the degree of tumor selectivity of Ad DNA replication only marginally influences antitumoral immune responses, but strongly determines anti-vector immunity and systemic toxicity in mice (27). However, whereas replication of viral DNA was an essential precondition for the efficacy of ODC, as shown in our previous experiments, we observed no differences in the antitumoral immune responses in all tumor models (Figure 6), which indicates that de novo gen- Figure 7A), confirming the absence of substantial viral infection and DNA replication in lung colonies.…”
Section: Vaccination On Day 3 (supporting
confidence: 81%
“…In contrast to rdAd, the unselective Ad5-WT and the tumor-selective hTert-Ad induced similar lysis in all investigated tumor cells in vitro and in vivo (data not shown). Interestingly, we observed no significant difference between hTert-Ad and Ad5-WT in ODC (Figure 6), in agreement with our previously described findings that the degree of tumor selectivity of Ad DNA replication only marginally influences antitumoral immune responses, but strongly determines anti-vector immunity and systemic toxicity in mice (27). However, whereas replication of viral DNA was an essential precondition for the efficacy of ODC, as shown in our previous experiments, we observed no differences in the antitumoral immune responses in all tumor models (Figure 6), which indicates that de novo gen- Figure 7A), confirming the absence of substantial viral infection and DNA replication in lung colonies.…”
Section: Vaccination On Day 3 (supporting
confidence: 81%
“…Interestingly, injection with Ad‐p53T viruses showed significantly decreased antiviral CD8‐specific immune responses and also the decreased antiviral cytotoxicity in liver. In contrast, no significant difference was identified for the antitumoral immune responses 22. Their study demonstrated the first piece of critical information for the immune responses induced by the tumor selective oncolytic adenoviruses.…”
Section: Discussionmentioning
confidence: 93%
“…For clinical use, multiple consecutive injections of oncolytic virus are recommended to achieve a more prominent effect 19, 20. However, its feasibility has not been investigated in the immunocompoent animal models established previously 21–24. Therefore, we proposed to address both issues using an immunocompetent HCC model of HBx transgenic mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitation of adenoviral infection by hexon quantitative PCR (qPCR) has been described elsewhere (31).…”
Section: Determination Of Viral Infection In Vivomentioning
confidence: 99%